2002
DOI: 10.1007/s11738-002-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of kinetin and spermidine in controlling salinity stress in mulberry (Morus alba L. cv. S1)

Abstract: In mulberry (Morus alba L.) plants NaCI stress imposed through roots by irrigation during growth period decreased the net photosynthetic rate (NPR), physiological water use efficiency (pWUE), which ultimately reflected on the reduction of growth parameters and leaf yield. Foliar spray of kinetin and spermidine ~both at 1 raM) on salinized plants reduced the detrimental effects of saline stress. Kinetin and spermidine sprayed plants increased the total chlorophyll, protein content, as well as leaf yield, but re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 15 publications
6
11
0
1
Order By: Relevance
“…Primary metabolites where N is the main component, such as amino acids, the building blocks in the synthesis of proteins, are involved in plant growth and development (Hounsome et al, 2008). Foliar application of amino acids increased the protein content in mulberry plants (Das et al, 2002). However, among the twenty three amino acids Ala, and Ser showed negative effects on the Eustoma seedlings by decreasing the leaf size and numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Primary metabolites where N is the main component, such as amino acids, the building blocks in the synthesis of proteins, are involved in plant growth and development (Hounsome et al, 2008). Foliar application of amino acids increased the protein content in mulberry plants (Das et al, 2002). However, among the twenty three amino acids Ala, and Ser showed negative effects on the Eustoma seedlings by decreasing the leaf size and numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Spraying with BA increased the area of leaves: for leaf 11 there was a gain of about 40% compared with an unsprayed leaf in 80 mM NaCl. BA does retard senescence of detached rice leaves (Yeh and Kao 1994) and spraying maize plants with kinetin does counteract effects of salinity El-Shihaby et al 2002;Khan and Srivastava 1998;Younis et al 2003) as is the case with wheat (Gadallah 1999) and mulberry (Das et al 2002), but not with rice (Yokoyama et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies showed that foliar application of AA increased plant protein content. For example, Das et al (2002) reported that foliar spray of mulberry plants with AA increased the protein contents as well as leaf yield as compared with the control plant. The positive increment in plant protein content due to AA application has also been recorded by Chang et al (2005).…”
Section: Introductionmentioning
confidence: 99%